Effects of strength vs. plyometric training on change of direction performance in experienced soccer players - Guldteig Rædergård, H.; Nygaard Falch, H.; van den Tillaar, R. (Sports, 2020)
The purpose of this study was to compare how 6 weeks of strength- vs. plyometric training, which were matched upon direction of motion and workload, influences change of direction (COD) performance. Twenty-one experienced male soccer players (age: 22.2 ± 2.7) were pair-matched into a strength- (n = 10) and a plyometric (n = 11) training group. CODs of 45°, 90°, 135° and 180° performed from either a 4 m or 20 m approach distance were compared before and after intervention. Results showed no significant difference between groups. Significant effects were only found within the plyometric training group (-3.2% to -4.6%) in 90°, 135° and 180° CODs from 4 m and a 180° COD from a 20 m approach distance. Individual changes in COD performances showed that with the 4 m approach at least 55% and 81% of the strength and plyometric training group, respectively, improved COD performance, while with the 20 m approach at least 66% of both groups improved performance. This study showed that the plyometric training program can improve most CODs, with angles over 90°, although this is dependent on the distance approaching the COD. Considering the limited time of implementing physical conditioning, in addition to regular soccer practice in most soccer environments, the current plyometric training program can be advantageous in improving CODs at maximal intensity.